Non Verbal Cues in Group Behavior amongst Youngsters (Global Journal of Management and Business Research, 2012)
This paper aims to study non verbal cues in group behavior amongst youngsters. For this analysis two groups (age ranging from 18-19 years) of 66 students, 45 boys and 21 girls were studied. They were studied at different time intervals and in different setting. It has been observed that there were various non verbal cues which were more prominent and expressive than the verbal interaction. The non verbal cues of the participants which occur throughout the interaction were more instrumental in shaping the group behavior than the verbal cues.
Keywords: Communication; non verbal cues; group interaction